Analysis of the Success of Cilembu Sweet Potatoes at Tawakal Mandiri UMKM in Penetrating the Domestis Market - Kartiwa, Aa; Aini, Alifia Syifa; Sulastri, Asri; Fitaloka, Dewi; Suryati, Suryati (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2026)
Cilembu sweet potato is a superior agricultural product originating from Tanjungsari, Sumedang Regency, West Java, known for its unique characteristics of natural sweetness and soft texture after baking. These advantages are the main attraction that drives increasing market demand, both at the local and national levels. This study was conducted to analyze the factors that influence the success of Cilembu sweet potato in penetrating the domestic market and examine the marketing strategies implemented by producers in expanding market reach. The research method used is a qualitative descriptive approach through interviews, field observations, and documentation. The results show that the success of Cilembu sweet potato in entering the domestic market is influenced by maintained product quality starting from the process of selecting sweet potatoes, maintaining quality taste, strengthening distribution networks, and implementing direct distribution channels, especially to meet domestic market needs.